Effects of Earth's gravitation and compressibility on co- and post-seismic deformations. Issue 3 (25th October 2022) - Liu, Tai; Tang, He; She, Yawen; Fu, Guangyu
SUMMARY: In this paper, we systematically analyse the effect of Earth's gravitation and compressibility on co- and post-seismic deformations. Based on the analytical solution of dislocation Love number (DLN) in a non-gravitational and incompressible homogeneous Earth model, it was seen that reducing the density of the homogeneous Earth model can provide results equivalent to a non-gravitational model while expanding the Lamé constant of the homogeneous model gives results equivalent to those from an incompressible model. Then, we applied a non-gravitational and incompressible treatment in a layered spherical Earth model, and calculated the co- and post-seismic Green's functions for four independent sources. It is found that the effect of Earth's gravitation and compressibility are dependent on source depth and time after the event. The effect of gravitation on the co-seismic Green's function of a shallow source is much smaller than that of compressibility, while the effect of gravitation on the post-seismic Green's function over longer timescales is much greater than that of compressibility. Finally, taking the 2011 Tohoku-Oki M w 9.0 and 2013 Okhotsk M w 8.3 earthquakes as examples, the simulation results show that post-seismic deformation studies should consider the Earth's compressibility, which is more obvious in the early post-seismic period. Likewise, when the viscosity of the study area is low, the effect of gravitation cannot be ignored. For the slip inversion of Tohoku-Oki M w 9.0 earthquake, the incompressible Earth model leads to a smaller slip magnitude than the compressible Earth model.